Effect of probiotic VEBAC on the growth of broilers - Ivanković, Stanko; Kralik, Gordana; Milaković, Zlata; Bogut, Ivan (Acta Agraria Kaposváriensis, 1999)
Eighty Avian 24K broilers were randomly divided in 2 groups, 40 birds each. Each group had 4 subgroups of 10 birds. First group was control (without VEBAC in drinking water), while second was experimental (with addition of VEBAC - 3 g/100 I water). Average live weights of Avian 24K chicken in age of 42 days were for 10.8% higher in 2nd group (3 g/100 I VEBAC) compared to the 1st group without probiotic in drinking water (2.19 kg : 1.96 kg; P<0.01). Growth curve showed thath addition of VEBAC in drinking water enhances progressive stage of growth. Probiotok addition resulted in more efficient conversion of food into live weight gain of chicken for 6.44% in 2nd group od chicken compared to the 1st group. Addition of VEBAC in drinking water had positive effect on performances of broilers. Usage of VEBAC shortened fattening for 0,6 weeks.